QUIZIZZ INTEGRATION IN ENGLISH LANGUAGE LEARNING TO INCREASE STUDENT’S VOCABULARY MASTERY - Rosyidatul Ulumiyah; M Labib Al Halim (FKIP, Universitas Billfath Lamongan, 2025)
Abstract: This research aims to test the effectiveness of learning media using quiz apk on vocabulary mastery. This study uses a quantitative approach with an experimental research design. The study was conducted at MTs Salafiyah Siman Sekaran class VIII. Data collection techniques were carried out with pre-test and post-test. The instrument used was a student worksheet with a multiple-choice model. The results of the study showed that there was a significant difference in the implementation of the pretest and posttest. This is evidenced by the increase in the average count of the pretest and posttest scores which increased with an average value of 90.13. In addition, based on the results of the t-test, it can be seen that sig (2-tailed) 0.000 is smaller than 0.05. Thus, it is stated that learning media using the Quizizz apk is effectively applied in the vocabulary mastery of class VIII students.